Multiday corticosteroids in cancer chemotherapy delay the diagnosis of and antimicrobial administration for febrile neutropenia: a double-center retrospective study - Hiroki Uda; Yukio Suga; Eriko Toriba; Angelina Yukiko Staub; Tsutomu Shimada; Yoshimichi Sai; Masami Kawahara; Ryo Matsusita (BMC, 2019)
Abstract Background Medical staff should promptly administer antimicrobials to patients with febrile neutropenia (FN) to decrease the mortality related to cancer chemotherapy. Corticosteroids, which are used in cancer chemotherapy, have a fever-suppressive effect. This effect could lead to a blunt fever response and any local signs of infection, especially in patients receiving multiday corticosteroid administration. The aim of this study was to determine whether multiday corticosteroid administration in cancer chemotherapy delays the diagnosis of and antimicrobial treatment for FN. Methods We conducted a double-center retrospective study in Japanese patients with FN. The patients were divided into two groups based on the corticosteroid administration method, i.e., whether administration was multiday or not. To evaluate the degree of masking on FN by corticosteroids, we assessed the correlation between body temperature variation and time of antimicrobial administration after the initiation of chemotherapy. Risk factors for delayed antimicrobial administration were identified by multiple logistic regression analysis. Results Two hundred thirteen patients were analyzed. The median time required to body temperature reaching 37.5 °C and for antimicrobial administration was longer in the multiday group than in the non-multiday group, with 0.64 and 0.60 days (P = 0.002 and P < 0.001), respectively. Multiday corticosteroid use was identified as an independent risk factor for delayed antimicrobial administration (odds ratio = 3.94; 95% confidence interval = 1.80-8.62; P < 0.001). Conclusions Multiday corticosteroid administration in cancer chemotherapy delayed the diagnosis of and antimicrobial administration for FN. Furthermore, it was the only risk factor for delayed antimicrobial administration. We could thus provide evidence that the diagnosis of and antimicrobial administration for FN in patients receiving multiday corticosteroid administration should not be based on body temperature variation alone.